Polimorlismo do gene GH (hormônio do crescimento) na produção de leite em bovinos da raça sintética Girolando - Franco, Rossana Vilela Rezende (2003)
The bovine growth hormone is a very important galactopoietic for dairy cattle, because it regulates milk production and stimuiates the mammary gland development. Recently a research focus has been done forwards the use of molecular markers associated to important economics characters in domestic animais. Th is research used 452 cows of the Brazilian breed “Girolando 5/8” from five Brazilian States aiming the analysis of the effects of the growth hormone gene polymorphism of the on milk yield. PCR reaction generated a 891 bp amplicon, which were submitted to restriction through the Msp I endonuclease. Genotyping was based on restriction fragment sizes. The allele C presented 4 fragments; 526 193, 109 and 63 bp, the allele D presented 3 fragments; 635, 193 and 63 bp. The genotypic frequencies were 0,3849; 0,4248 and 0,1903 for CC, CD and DD respectively, and allelic frequencies were 0,5973 for the allele C and 0,4027 for the allele D. Statistical analysis considering 299 animais, has shown significant differences for mean daily milk yield and total milk yeld. Logistic regression has calculated the allelic substitution effects, which demonstrated an increase in milk production by an average of 376 g/day/cow and 68,61 Kg/lactation/cow for each allele C incorporated. The results suggest that this polymorphism may be useful for marker assisted selection in Brazilian breed “Girolando”.